The likeness of fetal growth and newborn size across non-isolated populations in the INTERGROWTH-21st Project: the Fetal Growth Longitudinal Study and Newborn Cross-Sectional Study. - Villar, J; Papageorghiou, A; Pang, R; Ohuma, E; Cheikh Ismail, L; Barros, F; Lambert, A; Carvalho, M; Jaffer, Y; Bertino, E; Gravett, MG; Altman, D; et al. (2014)
BACKGROUND: Large differences exist in size at birth and in rates of impaired fetal growth worldwide. The relative effects of nutrition, disease, the environment, and genetics on these differences are often debated. In clinical practice, various references are often used to assess fetal growth and newborn size across populations and ethnic origins, whereas international standards for assessing growth in infants and children have been established. In the INTERGROWTH-21(st) Project, our aim was to assess fetal growth and newborn size in eight geographically defined urban populations in which the health and nutrition needs of mothers were met and adequate antenatal care was provided. METHODS: For this study, fetal growth and newborn size were measured in two INTERGROWTH-21(st) component studies using prespecified markers and the same methods, equipment, and selection criteria. In the Fetal Growth Longitudinal Study (FGLS), we studied educated, affluent, healthy women, with adequate nutritional status who were at low risk of intrauterine growth restriction. The primary markers of fetal growth were ultrasound measurements of fetal crown-rump length at less than 14 weeks and 0 days of gestation and fetal head circumference from 14 weeks and 0 days to 40 weeks and 0 days of gestation, and birthlength for newborn size. In the concomitant, population-based Newborn Cross-Sectional Study (NCSS), we measured birthlength in all newborn babies from the eight geographically defined urban populations with the same methods, instruments, and staff as in FGLS. From this large NCSS cohort, we selected an FGLS-like subpopulation to match FGLS with the same eligibility criteria. FINDINGS: Between May 14, 2009, and Aug 2, 2013, we enrolled 4607 women in FGLS and 59 137 women in NCSS. From NCSS, 20 486 (34·6%) women met the FGLS eligibility criteria, and constituted the FGLS-like subpopulation. With variance component analysis, only between 1·9% and 3·5% of the total variability in crown-rump length, fetal head circumference, and newborn birthlength could be attributed to between-site differences. With standardised site effect analysis in 16 gestational age windows from 9 weeks and 0 days of gestation to birth for the three measures (128 comparisons), only one was marginally higher than 0·5 SD of the standardised site difference range. Sensitivity analyses, excluding individual populations in turn from the pooling of all-site centiles across gestational ages, showed no noticeable effect on the 3rd, 50th, and 97th centiles derived from the remaining populations. Our populations were consistent at birth with those in the WHO Multicentre Growth Reference Study (MGRS). The mean birthlength for term newborn babies in that study was 49·5 cm (SD 1·9), which was very similar to that in the FGLS cohort (49·4 cm [1·9]) and the NCSS derived FGLS-like subpopulation (49·3 cm [1·8]). INTERPRETATION: Fetal growth and newborn length are similar across diverse geographical settings when mothers' nutritional and health needs are met, and environmental constraints on growth are low. The findings for birthlength are in strong agreement with those of the WHO MGRS. These results provide the conceptual frame to create international standards for growth from conception to newborn baby, which will extend the present infant to childhood WHO MGRS standards. FUNDING: Bill and Melinda Gates Foundation.